First, we need to simplify the expression inside the parentheses:
3 1/3 - 2 1/4
= (10/3) - (9/4) (converting mixed fractions to improper fractions)
= (40/12) - (27/12) (getting a common denominator)
= 13/12
Now, we can calculate 7/6 of (13/12):
(7/6) × (13/12)
= (91/72)
Next, we need to simplify the expression after the plus sign:
5 1/8 ÷ 3/16 - 1/2
= 41/8 ÷ 3/16 - 1/2 (converting mixed fractions to improper fractions)
= 41/8 × 16/3 - 1/2 (dividing by a fraction is the same as multiplying by its reciprocal)
= 82/3 - 1/2
= (164/6) - (3/6) (getting a common denominator)
= 161/6
Finally, we can add the two simplified expressions:
(91/72) + (161/6)
= (13/72) + (26/72) + (241/72) (getting a common denominator)
= 280/72
= 35/9
Therefore, the value of the expression is 35/9.
Determine the value of 7/6 of (3 1/3 -2 1/4)+5 1/8÷3/16-1/2
1 answer